ICAT-EGVE 2018 (Merger of the 28th International Conference on Artificial Reality and Telexistence (ICAT 2018) and the 23rd Eurographics Symposium on Virtual Environments (EGVE 2018)) - Michael-Grigoriou, Despina (My University, 2026)
General Chair (Lead)